Respuesta :

Answer: 9^-16

Step-by-step explanation:

a^b*a^c= a^b+c

The answer is 9⁻¹⁶

Since we need to find 9⁻⁵³ . 9³⁷, from the law of exponents, we have that for any two numbers xᵃ  and xᵇ,

xᵃ .xᵇ = xᵃ⁺ᵇ.

So, for any two numbers with the same base, when multiplying them together, we add the exponents together.

So, given 9⁻⁵³ . 9³⁷

9⁻⁵³ . 9³⁷ = 9⁻⁵³ ⁺ ³⁷ (adding the exponents together, we have)

9⁻⁵³ . 9³⁷ = 9⁻¹⁶

So, our answer is 9⁻¹⁶.

So, to simplify the expression 9⁻⁵³ . 9³⁷ we have 9⁻¹⁶

So, 9⁻⁵³ . 9³⁷ = 9⁻¹⁶

Thus, our answer is 9⁻¹⁶

Learn more about exponents here:

https://brainly.com/question/13903967